Christian Religious Studies Curriculum Implementation: Do Teacher’s Activities, Students’ Activities, and Instructional Materials Matter? (British Journal of Multidisciplinary and Advanced Studies, 2025)
Teacher’s activities, students’ activities, and instructional materials are instrumental to successful curriculum implementation, and students’ academic performance. This study examined Christian Religious Studies Curriculum Implementation: Do Teacher’s Activities, Students’ Activities, and Instructional Materials Matter? The sample of one hundred and twenty students and eight teachers was selected from the public Secondary Schools in Ado-Ekiti, Ekiti State. Two instruments were used for data collection: questionnaire and CRS Achievement Test (CRSAT). The data collected was analyzed using descriptive statistics of simple percentage, mean and standard deviation to answer the research questions, while inferential statistics of t-test and linear regression were used to test the hypotheses. Findings from the study showed that both the CRS teachers and students are performing their respective activities as indicated in the CRS curriculum, and that the CRS students’ activities in curriculum implementation have no significant influence on the academic performance of CRS students. It was recommended that researchers and stakeholders in education industry should look beyond the CRS curriculum implementation in finding solutions to the unsatisfactory academic performance of the CRS students at the senior secondary classes in Ekiti State public secondary schools.